Enhanced distribution and mechanical properties of high content nanoparticles reinforced metal matrix composite prepared by flake dispersion. (1st March 2023) - He, Hongyun; Fan, Genlian; Saba, Farhad; Tan, Zhanqiu; Su, Zhu; Xiong, Dingbang; Li, Zhiqiang
Abstract: Achieving a uniform dispersion and high efficiency in metal matrix nanocomposites (MMNCs) with a high-content of nano-reinforcements is still a challenging issue. Flake dispersion, a fabrication process combining flake powder metallurgy with high-shear dispersion, is proposed to alleviate the problem. In this regard, flake Al powders with a large specific surface-area were used as a core to be coated with a high content of SiC nanoparticles through the well-established high-shear dispersion process. The produced SiCnp /Al nanocomposites, reinforced with 5 wt% and 10 wt% SiCnp, showed a uniform distribution of intragranular nanoparticles within an ultrafine-grained matrix. Furthermore, the 10 wt% SiCnp /Al nanocomposite exhibited a yield strength of 306 MPa and an ultimate tensile strength of 420 MPa, which were, respectively, 191% and 202% higher than the unreinforced matrix. Meanwhile, the composite maintained an acceptable fracture elongation (up to 10.8%) which can be attributed to the homogeneous and intragranular distribution of nanoparticles in the matrix. The results authenticated that flake dispersion is an efficient strategy to derive synergistic effects contributing to simultaneously enhancing strength and ductility in MMNCs. Graphical abstract: Image 1 Highlights: Flake dispersion constructed uniform intragranular dispersion of SiCnp efficiently. Nanocomposites produced by flake dispersion achieved synergy of strength and ductility. The dominant strengthening mechanism was Orowan strengthening. Uniform dispersion contributes to more uniform deformation and energy dissipation.